2010
DOI: 10.1111/j.1365-2109.2010.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation and reuse of shrimp aquaculture effluents to farm whiteleg shrimp, Litopenaeus vannamei : a first approach

Abstract: Shrimp aquaculture e¥uents were bioremediated in a two-phase system (System A) using the black clam Chione £uctifraga and the benthic microalgae Navicula sp., and then reused to farm whiteleg shrimp Litopenaeus vannamei. In the experimental design, Systems B and C had an identical structure as System A, but no clams or microalgae were added. System B received the same shrimp e¥uents while System C received only estuarine water. Shrimp raw e¥uents had a poor water quality. System A improved the water quality by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…La tasa de crecimiento del camarón obtenida en este trabajo fue del 3,8% día -1 , similar a la obtenida por Anaya-Rosas & Bückle-Ramírez (2012) de 3,7% día -1 , en un cultivo intensivo en sistema de recirculación de agua y fue mayor a la reportada por Martínez-Córdova et al (2010) para un cultivo multitrófico experimental con camarón L. vannamei, almeja Chione fluctifraga y la microalga Navicula sp. Lezama-Cervantes et al (2010) evaluaron el uso de tapetes microbianos como biofiltro en un cultivo de camarón con recirculación de agua y concluyeron que el uso de agua biorremediada tuvo un efecto positivo en el crecimiento y en la sobrevivencia de L. vannamei.…”
Section: Discussionunclassified
“…La tasa de crecimiento del camarón obtenida en este trabajo fue del 3,8% día -1 , similar a la obtenida por Anaya-Rosas & Bückle-Ramírez (2012) de 3,7% día -1 , en un cultivo intensivo en sistema de recirculación de agua y fue mayor a la reportada por Martínez-Córdova et al (2010) para un cultivo multitrófico experimental con camarón L. vannamei, almeja Chione fluctifraga y la microalga Navicula sp. Lezama-Cervantes et al (2010) evaluaron el uso de tapetes microbianos como biofiltro en un cultivo de camarón con recirculación de agua y concluyeron que el uso de agua biorremediada tuvo un efecto positivo en el crecimiento y en la sobrevivencia de L. vannamei.…”
Section: Discussionunclassified
“…In Northwest Mexico, semi-intensive systems have shown a broad range [ 38 ] and obtained an average of 45 m 3 kg −1 cycle −1 with 7% daily water exchange; Casillas-Hernández et al [ 9 ] obtained 62–71 m 3 kg −1 cycle −1 with daily turnover of 11%; Miranda et al [ 13 ] reported values of 101–105 m 3 kg −1 cycle −1 with a turnover of 13% day −1 . Studies in shrimp cultures with low water exchange in Mexico have reported rates of 9 to 17 m 3 kg −1 cycle −1 with 3–5% daily turnover [ 19 ], 17 to 38 m 3 kg −1 cycle −1 with 5% daily turnover in 140-day cycles [ 15 ], and 17 to 21 m 3 kg −1 cycle −1 with 5% daily turnover in of 120-day cycles [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…High turnover rate allows for some water quality variables to be well regulated in terms of water quality; it nevertheless represents a massive waste of potentially useful nutrients and organic matter. Martínez-Córdova et al [ 15 ] demonstrated experimentally that it is possible to reuse the effluent of semi-intensive ponds to grow bivalves, benthic diatoms, and whiteleg shrimp ( Litopenaeus vannamei ) in a multitrophic system. Nevertheless, this practice requires validation for use on a commercial scale because the effects on water quality and productive performance of shrimp, as well as N recycling and discharge, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Grow‐out techniques for farming C. fluctifraga have not been developed. Management experiments with this clam included collection of adult clams (30–35 mm height) and cultivation on the bottom of shrimp ponds was done to evaluate: (i) feasibility of polycultivation with whiteleg shrimp Litopenaeus vannamei and the Pacific oyster Crassostrea gigas (Martínez‐Córdova & Martínez‐Porchas ), and (ii) bioremediation of shrimp pond effluent (Martínez‐Córdova, López Elías, Martínez‐Porchas, Bernal‐Jaspeado & Miranda Baeza ; Martínez‐Córdova, López‐Elías, Leyva‐Miranda, Armenta‐Ayon & Martínez‐Porchas ). Juvenile clams (20 mm height) collected from mudflats were cultivated in floating trays during winter in shrimp ponds (Martínez‐Córdova, Enríquez‐Ocaña, López‐Rascón, López‐Elías & Martínez‐Porchas ).…”
Section: Discussionmentioning
confidence: 99%